2016
DOI: 10.1073/pnas.1523681113
|View full text |Cite
|
Sign up to set email alerts
|

Tissue nonautonomous effects of fat body methionine metabolism on imaginal disc repair in Drosophila

Abstract: Regulatory mechanisms for tissue repair and regeneration within damaged tissue have been extensively studied. However, the systemic regulation of tissue repair remains poorly understood. To elucidate tissue nonautonomous control of repair process, it is essential to induce local damage, independent of genetic manipulations in uninjured parts of the body. Herein, we develop a system in Drosophila for spatiotemporal tissue injury using a temperature-sensitive form of diphtheria toxin A domain driven by the Q sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 39 publications
2
32
0
Order By: Relevance
“…As we expected, we found a decrease in methionine and SAM, and an increase in SAH in the fat body after disc ablation, particularly in the early stage of disc repair (6 h after ablation) 3 . These data suggest that methionine metabolism in the fat body responds to local tissue damage in wing discs.…”
Section: Introductionsupporting
confidence: 86%
See 2 more Smart Citations
“…As we expected, we found a decrease in methionine and SAM, and an increase in SAH in the fat body after disc ablation, particularly in the early stage of disc repair (6 h after ablation) 3 . These data suggest that methionine metabolism in the fat body responds to local tissue damage in wing discs.…”
Section: Introductionsupporting
confidence: 86%
“…Functional contributions to tissue repair could be assessed by combining Q-dependent DtA ts -induced wing disc ablation and a fat body Gal4 driver 3 . As we reported, both knockdown and overexpression of gnmt or sams in the fat body impaired the repair of wing discs, while these genetic manipulations had no apparent effects on normal wing development.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Based on this, we suggest that tissue‐specific dysregulation of methionine metabolism can be a driving force of age‐dependent intestinal dysplasia and further, that either MetR or activation of methionine flux can prevent these changes, improve proliferative homeostasis, and extend lifespan. Furthermore, Kashio et al () found that alterations of SAM metabolism in the fat body via up‐ or downregulation of GNMT affect repair of wing disks, showing that organ‐specific changes in methionine metabolism have systemic effects on regenerative processes. It will be of interest to further understand how methionine metabolism is altered with age in different organs and create genetic tools that will allow dissection of the role(s) of methionine metabolism in specific tissues and organs.…”
Section: Methionine Metabolism and Lifespan Extension In Drosophila Mmentioning
confidence: 99%
“…Kashio et al examined the systemic effects of local tissue damage in the wing disc epithelium and found that methionine metabolism changed in the fat body, which is a Drosophila adipose tissue. The altered methionine metabolism is required for wing disc tissue repair, suggesting that local apoptosis is linked to the fat body metabolism via systemic factors [92]. These findings suggest that apoptotic cells systematically influence homeostasis of the whole body and overall organism health.…”
Section: Future Directionsmentioning
confidence: 99%